2016
DOI: 10.18632/oncotarget.13458
|View full text |Cite
|
Sign up to set email alerts
|

EGFR kinase inhibitors and gastric acid suppressants in EGFR-mutant NSCLC: a retrospective database analysis of potential drug interaction

Abstract: BackgroundErlotinib and gefitinib are weak base drugs whose absorption and clinical efficacy may be impaired by concomitant gastric acid suppressive (AS) therapy, yet proton pump inhibitors (PPIs) and histamine-2 receptor antagonists (H2As) are widely indicated in non-small cell lung cancer (NSCLC) patients for the prevention and treatment of erlotinib-induced gastrointestinal injury and corticosteroid-associated gastric irritation. We assessed the clinical relevance of this potential drug-drug interaction (DD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 34 publications
0
38
0
Order By: Relevance
“…Of note, in that study 26 , patients were unselected for activating EGFR mutations. Two retrospective cohort studies 11,27 , involving 157 and 130 patients treated with erlotinib or gefitinib, respectively, for the treatment of EGFR mutation-positive advanced NSCLC have been conducted. These studies showed that the combination of EGFR-TKIs with antacid did not affect the efficacy of erlotinib and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in that study 26 , patients were unselected for activating EGFR mutations. Two retrospective cohort studies 11,27 , involving 157 and 130 patients treated with erlotinib or gefitinib, respectively, for the treatment of EGFR mutation-positive advanced NSCLC have been conducted. These studies showed that the combination of EGFR-TKIs with antacid did not affect the efficacy of erlotinib and gefitinib.…”
Section: Discussionmentioning
confidence: 99%
“…25 In a more recent retrospective database analysis of 157 patients with EGFR mutation-positive NSCLC treated with gefitinib or erlotinib, concomitant gastric acid suppressive therapy was not found to have an adverse impact on overall survival or progression-free survival. 26 Similar results were found in another review of 130 patients with advanced EGFR mutationpositive NSCLC treated with gefitinib or erlotinib (of whom 47 received gastric acid suppressive therapy), with no significant differences found in objective response rate (64% in those who received gastric acid suppressive therapy versus 63% in those who did not; P = .92), median progression-free survival (8.7 versus 10.7 months, respectively; P = .13), or toxicity. 27 Larger long-term studies to investigate further the clinical impact of elevated gastric pH from gastric acid suppressive agents or physiological conditions on the efficacy of gefitinib are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 353 potentially eligible records were identified in the electronic databases. After exclusion of n=337 not pertinent papers, n=16 were selected for inclusion in quantitative analysis (n=372,418 patients included, with 12% of patients receiving concomitant GAS therapy) [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The search results and characteristics of the included studies are presented in figure 1 and tables 1-2.…”
Section: Resultsmentioning
confidence: 99%